PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII B2 MTs DARUL HIKMAH PEKANBARU - Sofiana, Yulia; Kartini, Kartini; Sakur, Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research is to improve the students achivement of math at class VII B2 MTs Darul Hikmah Pekanbaru through apply of cooperative learning model struktural approach of Numbered Heads Together. This research is classroom action research with two cycles including planning, implementation, observation and reflection. The success of the action is marked by improved of the learning process and increase of achievement. Improvement of the learning process can be seen from the reflection of observations result and increased of achievement marked by value of student's individual progress and reaching of KKM score. The results of research showed activity of teacher and students improved after doing an action. Number of students who reach a score of KKM on UH in the end of each cycle increase compared to the number of students who reach a score of KKM on base score and the number of students who get value of individual progress 20 and 30 more than the number of students who get value of individual progress 5 and 10 also increased an average value of student achievement from base score. The results of this research show that apply of cooperative learning model structural approach of NHT make a change in the learning process and increased students achivement of math at class VII B2 MTs Darul Hikmah Pekanbaru. Based on these results, apply of cooperative learning model structural approach of NHT can improve students achivement of math.Key words: numbered heads together, cooperative learning, achievement